PENGARUH PENGGUNAAN METODE GLOBAL TERHADAP PENINGKATAN KEMAMPUAN MEMBACA WARGA BELAJAR DI RUMAH BELAJAR PINTAR DESA KLAMBIR LIMA KEBUN - Ayu Iga Ardini; Sani Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was conducted with three main objectives: first, to analyze the implementation of the global method in improving the reading skills of learners at Rumah Belajar Pintar, Klambir Lima Kebun Village; second, to examine the extent of reading skill improvement that can be achieved through the application of the global method at the site; and third, to analyze the influence of the global method on enhancing the reading skills of learners at Rumah Belajar Pintar, Klambir Lima Kebun Village. The study involved a sample of 25 learners selected using the total sampling method, thus including the entire population as research subjects. Data for the study were collected using two primary instruments: questionnaires and observation sheets, to obtain accurate and relevant information regarding the implementation of the global method and its impact on the learners’ reading skills. The collected data were then analyzed using linear regression to determine the extent of the influence of the global method on the learners' reading skills. The results of the study revealed a significant influence of the global method on the improvement of learners' reading skills, with an influence value of 4.791. These findings demonstrate that the global method has a considerable impact on helping learners enhance their reading skills. Based on these results, it is recommended that educators adopt a more active and consistent approach to using the global method as one of the strategies for teaching reading to learners. This approach is expected to contribute to improving the quality of learning and the reading abilities of the learners.